A novel synthesis of trans-unsaturated fatty acids by the Gram-positive commensal bacterium Enterococcus faecalis FA2-2. (August 2019) - Kondakova, Tatiana; Kumar, Sneha; Cronan, John E.
Highlights: For the first time we demonstrate the production of trans -unsaturated fatty acids by a Gram-positive bacterium. The mechanism of trans -UFA production was investigated. The role of trans -unsaturated fatty acids in E. faecalis FA2-2 remains unresolved. Organic solvents, as well as daptomycin failed to activate trans -UFA production in E. faecalis FA2-. Abstract: A key mechanism of Pseudomonas spp. adaptation to environmental stressors is their ability to convert the cis -unsaturated fatty acids of the membrane lipids to their trans -isomers to rigidify the membrane and thereby resist stresses. Although this Cti-catalyzed enzymatic isomerization has been well investigated in the P. putida paradigm, several bacterial species have been found to produce trans -unsaturated fatty acids. Although cti orthologs have only been reported in Gram-negative bacteria, we report that E. faecalis FA2-2 cultures synthesize trans -unsaturated fatty acids during growth by a mechanism similar of P. putida . Although the role of trans -unsaturated fatty acids (trans -UFAs) in E. faecalis remains obscure, our results indicate that organic solvents, as well as the membrane altering antibiotic, daptomycin, had no effect on trans -UFA formation in E. faecalis FA2-2. Moreover trans -UFA production in E. faecalis FA2-2 membranes was constant in oxidative stress conditions or when metal chelator EDTA was added, raising the question about the role of heme domain in cis-trans isomerization in E. faecalis FA2-2. Although growth temperature and growth phase had significant effects on cis-trans isomerization, the bulk physical properties of the membranes seems unlikely to be altered by the low levels of trans -UFA. Hence, any effects seems likely to be on membrane proteins and membrane enzyme activities. We also report investigations of cti gene distribution in bacteria was and suggest the distribution to be triggered by habitat population associations. Three major Cti clusters were defined, corresponding to Pseudomonas, Pseudoalteromonas and Vibrio Cti proteins.